Heterobilharzia americana infection in dogs: A retrospective study of 60 cases (2010‐2019). (2nd May 2021) - Graham, Amber M.; Davenport, Amy; Moshnikova, Valentina S.; Gilmour, Lindsey J.; Fabiani, Michelle; Bishop, Micah A.; Cook, Audrey K.
Abstract: Background: The trematode Heterobilharzia americana ( HA ) causes granulomatous gastrointestinal and hepatic disease in dogs. Before 2008, diagnosis relied on saline fecal sedimentation or histopathology, and earlier reports primarily described dogs with advanced disease or cases diagnosed incidentally at necropsy. The advent of a fecal PCR test has facilitated the diagnosis of HA and provided insights into manifestations and response to treatment. Objectives: Describe the clinical findings, response to treatment, and outcome for dogs infected with HA . Animals: Sixty dogs diagnosed with HA between 2010 and 2019. Methods: Retrospective study. Medical records were searched for dogs diagnosed with HA by fecal PCR testing, identification of ova in feces, or histopathology. Results: Mean age was 7.5 (±4.1) years and weight was 23.2 (±10.18) kg. Clinical signs included diarrhea (55.8%), vomiting (46.2%), and weight loss with or without anorexia (15.4%). Laboratory abnormalities included hyperglobulinemia (42.6%) and increased liver enzyme activities (30%). More than 40% of dogs had an eosinophil count >500/μL. Hypercalcemia attributable to HA was identified in only 4 dogs. Pinpoint hyperechoic foci were noted in intestines, liver, or mesenteric lymph nodes during transabdominal ultrasonography in 64.4% of dogs. Survival data was available for 34 dogs, of which 73.5% (25) were alive 6 months after diagnosis. Conclusions and Clinical Importance: Hyperglobulinemia, high eosinophil count, and ultrasonographic evidence of visceral mineralization were suggestive of infection. Hypercalcemia was uncommon. Combination treatment with praziquantel and fenbendazole was variably effective, and 17.6% of treated dogs with known outcome died as a result of HA infection.